Pharmacodynamic monitoring of cyclosporin A reveals risk of opportunistic infections and malignancies in renal transplant recipients 65 years and older - Sommerer, Claudia; Schnitzler, Paul; Meuer, Stefan; Zeier, Martin; Giese, Thomas (Therapeutic drug monitoring, 2011)
Background: - The cohort of senior renal allograft recipients is increasing. Age-related physiologic changes are believed to influence the pharmacokinetics and pharmacodynamics of immunosuppression. Measuring the residual nuclear factor of activated T-cell (NFAT)-regulated gene expression (RGE) is a promising pharmacodynamic tool to individually monitor cyclosporin A (CsA) therapy. - Patients and Methods: - In stable senior renal allograft recipients (≥65 years), the expression of 3 calcineurin-dependent NFAT-regulated genes (interleukin-2, interferon-γ, and granulocyte-macrophage colony-stimulating factor) was measured in whole-blood samples before (C0) and 2 hours (C2) after oral drug intake. Clinical data on opportunistic infections were collected in a clinical observational period of 12 months. - Results: - Thirty-six senior patients [22 male, median age 70 years (65-77)] were enrolled in this clinical study. Median daily CsA dosage was 150 mg (50-250), CsA C0 concentration 102 mcg/L (range 33-157), and CsA C2 concentration 551 mcg/L (range 254-1228). The NFAT RGE varied between 3% and 37% (median 10%). CsA peak concentrations and inhibition of gene expression correlated significantly (r = −0.737, P < 0.001). NFAT RGE in patients with opportunistic infections including atypical pneumonia, cytomegalovirus and herpes viral infections was lower compared with that in patients without infections [4% (3-13) versus 11% (3-37), P = 0.05], whereas the daily CsA dosage, CsA C0, and CsA C2 concentrations were comparable. Renal allograft function correlated inversely with NFAT RGE. - Conclusions: - A higher degree of immunosuppression correlated with more infectious complications in a considerable proportion of senior renal allograft recipients treated with standard CsA therapy. Pharmacodynamic monitoring is an approach to individualize immunosuppression and could provide the opportunity to reduce complications caused by infections.